Neutrophil Heterogeneity as Therapeutic Opportunity in Immune-Mediated Disease - Grieshaber-Bouyer, Ricardo; Nigrovic, Peter A. (Frontiers in Immunology, 2019)
Neutrophils are versatile innate effector cells essential for immune defense but also responsible for pathologic inflammation. This dual role complicates therapeutic targeting. However, neither neutrophils themselves nor the pathways they employ as immune effectors are homogeneous, suggesting possibilities for selective intervention. Here we review heterogeneity within the neutrophil population as well as in the pathways mediating neutrophil recruitment to inflamed tissues with a view to outlining opportunities for therapeutic manipulation in inflammatory disease.